Some Reliability Measures of a Deteriorating System - Yusuf, Ibrahim; Hussaini, Nafiu; Yakasai, Bashir M. (International Journal of Applied Mathematical Research, 2014)
In this paper, we studied some reliability characteristics of a repairable 3-out-of-4 system with three modes: normal, deterioration and failure modes. The deterioration mode could be slow or fast. Failure and repair time are assumed to be exponential. We develop the explicit expressions for steady-state availability, busy period of repair man, profit function and mean time to system failure for the system using linear first order differential equations. Various cases are analyzed graphically to investigate the impact of system parameters on MTSF and profit function.   Keywords: Reliability, availability, profit, deterioration.